2010
DOI: 10.1159/000318862
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Cancer Stem-Like Cells and Cancer-Associated Genetic Markers for Peritoneal Recurrence of Colorectal Cancer in Patients after Curative Surgery

Abstract: Objective: The new concept of cancer stem cells has implications in terms of possible application for novel diagnostic and therapeutic procedures. Recently, the CD133 molecule was reported as a marker of cancer stem-like cells in colorectal cancer (CRC). In this study, we examined the prognostic value of free cancer cells in peritoneal washings from CRC patients after curative resection using multiple molecular markers, including cancer stem-like cells. Methods: A total of 170 CRC patients who had undergone cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Iinuma showed that peripheral blood CD133 mRNA was the most prognostic when combined with CK and CEA via RT-PCR in 735 stage II and III colorectal cancer patients. Interestingly, CD133 mRNA alone was reportedly not prognostic by Iinuma in stage II and III colorectal cancer, but was prognostic in two other studies that included stage IV patients [71••, 72, 73]. Earlier-stage diseases, small sample size, possibly technical difference, and timing of CD133 mRNA acquisition (preoperative vs postoperative) may explain the differences why CD133 mRNA was not prognostic in the current study.…”
Section: Prognostic Values Of Cd133 Expression In Cancer and In Peripcontrasting
confidence: 57%
“…Iinuma showed that peripheral blood CD133 mRNA was the most prognostic when combined with CK and CEA via RT-PCR in 735 stage II and III colorectal cancer patients. Interestingly, CD133 mRNA alone was reportedly not prognostic by Iinuma in stage II and III colorectal cancer, but was prognostic in two other studies that included stage IV patients [71••, 72, 73]. Earlier-stage diseases, small sample size, possibly technical difference, and timing of CD133 mRNA acquisition (preoperative vs postoperative) may explain the differences why CD133 mRNA was not prognostic in the current study.…”
Section: Prognostic Values Of Cd133 Expression In Cancer and In Peripcontrasting
confidence: 57%
“…Moreover, patients who suffered from deeper invasion were inclined to have a higher level of CD133 mRNA expression after surgery ( P = 0.039). This result was similar to some other reports [28, 29]. Iinuma et al [28] found that the patients with Dukes' B or C of colorectal cancer, who had undergone curative surgery, could possess a higher level of CD133 mRNA in PBMCs.…”
Section: Discussionsupporting
confidence: 91%
“…One of the Fcs of CEA, CK20, and/or CD133 that exceeded cut-off value in patient group indicated the presence of the CTC (CTC (+)), as defined previously in studies by Iinuma [13, 17]. Fc below cut-off value denoted lack of CTC (CTC (−)).…”
Section: Methodsmentioning
confidence: 90%
“…Previous studies by Nakamura et al [13] and Iinuma et al [11] have shown that expression of CEA/CK20/CD133 mRNA was a useful tool for the detection of CTC in PB of colorectal cancer patients. Based on these studies, we measured the transcriptional levels of three genes: carcinoembryonic antigen [ CEA ], cytokeratin-20 [ CK20 ], and prominin-1 [ CD133 ] by means of qPCR using the relative quantification method (ΔΔCt method) [14].…”
Section: Methodsmentioning
confidence: 99%